Metabolic syndrome associated with psoriasis vulgaris in adults: A hospital-based study - Konda Chandrasekhar; Girija Subramanian; Virali Gulla; Kaliaperumal Karthikeyan (Journal of Clinical and Scientific Research)
Background: Increased mortality is observed in psoriasis patients having metabolic syndrome (MetS). It is essential to identify the risk factors early so that morbidity and mortality can be reduced in patients with psoriasis. The present study intended to find out the presence of MetS in patients with psoriasis and the association between the severity of psoriasis with MetS. Methods: In this hospital-based prospective study, 46 consecutive adult patients attending the Dermatology Outpatient Department with the diagnosis of psoriasis vulgaris were screened for MetS. Results: MetS was significantly more common in psoriatic patients. MetS was present in 25/46 patients with psoriasis. The patients studied had hypertriglyceridaemia (10/46), arterial hypertension (21/46) and impaired fasting plasma glucose levels (8/46). MetS was noted in patients with moderate-to-severe PASI scores. Conclusions: In the present study, MetS was noted in >50% of patients with psoriasis vulgaris and MetS had a positive correlation with the severity of psoriasis and regular screening of patients with psoriasis is highly recommended.